2011
DOI: 10.1182/blood-2010-08-300954
|View full text |Cite
|
Sign up to set email alerts
|

DNAM-1 ligand expression on Ag-stimulated T lymphocytes is mediated by ROS-dependent activation of DNA-damage response: relevance for NK–T cell interaction

Abstract: IntroductionIn addition to their role in providing antitumor and antiviral immunity, 1 natural killer (NK) cells are also able to regulate the T-cell arm of the adaptive immune response by secreting different cytokines and chemokines. 2 Moreover, several studies have provided evidence of cognate cell-cell interactions between NK cells and various leukocyte types, including dendritic cells (DCs) and B and T lymphocytes. [3][4][5] Although NK cells have been thought to mainly promote adaptive immune responses, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
116
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(122 citation statements)
references
References 50 publications
6
116
0
Order By: Relevance
“…Also, productive infection of cells with the gammaherpesvirus Epstein-Barr virus is associated with up-regulation of the DNAM-1 ligand CD112 (25). Although the underlying mechanism of such virus-induced cellular response remains to be investigated, the cellular DNA damage response (DDR) may play a role, as many viruses, including herpesviruses and retroviruses, activate the DDR, and DDR activation has been reported to trigger DNAM-1 ligand up-regulation (26,(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Also, productive infection of cells with the gammaherpesvirus Epstein-Barr virus is associated with up-regulation of the DNAM-1 ligand CD112 (25). Although the underlying mechanism of such virus-induced cellular response remains to be investigated, the cellular DNA damage response (DDR) may play a role, as many viruses, including herpesviruses and retroviruses, activate the DDR, and DDR activation has been reported to trigger DNAM-1 ligand up-regulation (26,(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…33 As expected, the intensity of Nec-2 and PVR expression was inversely correlated, Nec-2 being expressed in almost 100% of cases and PVR being virtually absent, unlike, for example, superantigen-stimulated T cells which at the cell surface express only PVR with a mechanism involving a DNA-damage responsedependent pathway. 40 Our methodological approach used for NK cell enrichment and expansion, which is essential to obtain a sufficient number of effectors to pursue a program of adoptive cellular therapy, may be transferred into the clinic for experimental phase I/II studies based on the in vivo infusion of ex vivo expanded and activated NK cells for the control of MRD in ALL patients. The possible correlation between the intensity of expression of ligands for NK cell activating receptors and the susceptibility to lysis may help identify patients who may gain the most benefit from NK-based immunotherapy and from alloreactive donors in the context of haploidentical HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…To gain insights into the molecular mechanisms regulating the expression of activating ligands in infected cells, we investigated the role of DDR, a host cell pathway that positively affects the expression of activating ligands (35)(36)(37)(38)(39)(40)(41)(42)(43) and that it is activated by HCMV (26,27,(29)(30)(31)(32)(33)(34). Nevertheless, in HCMV-infected HFFs, MICA, ULBP3, and PVR were still increased even when ATM, ATR, and/or DNA-PK were knocked down, thus indicating that these DDR kinases are not involved in the HCMV-mediated ligand stimulation, similar to what has been reported for murine NKG2DL during murine CMV infection (78).…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies reported that HCMV manipulates the DDR (26,27,(29)(30)(31)(32)(33)(34), a pathway able to stimulate NKG2DL and DNAM-1L expression as well (35)(36)(37)(38)(39)(40)(41)(42)(43), we examined the involvement of DDR signaling in the HCMV-mediated upregulation of activating ligands using genetic and pharmacological approaches.…”
Section: Nkg2d and Dnam-1 Ligands Contribute To The Nk Cell-mediated mentioning
confidence: 99%
See 1 more Smart Citation